The usage of building information modelling (BIM) in Malaysia's architecture industry - M.F.I Mohd-Nor; Tahir M.M.; I.M.S. Usman; Abdul Halim Ismail (Penerbit Universiti Kebangsaan Malaysia, 2019)
Over the last few decades, the architecture field have seen tremendous developments in skills level, work processes and professional culture with the adoption of computer software technologies. Investment in technology has always been to increase effectiveness and overall performance in the design and construction process that results in a return of investment. Today, more and more digital technologies have been developed and created to accommodate the high demands of the market over the years, including Building Information Modelling (BIM). This research paper aims to look into the insight of how architect firms in Malaysia are coping up with the adoption of BIM in the country. This research was originally conducted in 2013-14 and has seen its preliminary findings published over the years. However, this paper uncovers the sequential parts of the research that has yet to be published. The main data collecting instrument used was a nationwide survey that was conducted on all the architectural firms in Malaysia and the findings was used as a foundation for subsequent research phases on the subject matter. From the findings, it is revealed that BIM-based practice is still at an infancy level and that the industry and government bodies need to put on greater effort and produce better strategies to make BIM an industry standard technology.